Stabilisasi Tanah Lunak Menggunakan Campuran Ferronickle Slag dan Alkali - Soma Shaki Hadi Nugraha; Dzulfikar Sani; Lisa Fitriyana; Juny Andry Sulistyo (Journal of Engineering and Applied Technology, 2026)
The Kendal Industrial Park (KIK), Central Java, is characterized by soft clay soil with low bearing capacity, requiring improvement before being used as a construction foundation. This study aims to determine soil classification, analyze the effect of ferronickel slag and alkali (NaOH and KOH) mixtures, and evaluate the potential of these mixtures as soil stabilization materials. The research was conducted experimentally in the laboratory through specific gravity tests, grain size distribution analysis, Atterberg limits, Standard Proctor compaction test, direct shear test, and California Bearing Ratio (CBR) test. The mixture variations used consisted of 10% ferronickel slag combined with alkali solutions of NaOH and KOH at concentrations of 6%, 8%, and 10%. The results showed that the original soil was classified as fine-grained soil with high plasticity and a CBR value of 5.6%, indicating low bearing capacity. The addition of ferronickel slag and alkali reduced soil plasticity and increased soil strength and bearing capacity. Therefore, the mixture of ferronickel slag and alkali has the potential to be used as an environmentally friendly alternative soil stabilization material.